2020
DOI: 10.3390/pathogens9090739
|View full text |Cite
|
Sign up to set email alerts
|

Immune Response to COVID-19: Can We Benefit from the SARS-CoV and MERS-CoV Pandemic Experience?

Abstract: The global range and high fatality rate of the newest human coronavirus (HCoV) pandemic has made SARS-CoV-2 the focus of the scientific world. Next-generation sequencing of the viral genome and a phylogenetic analysis have shown the high homology of SARS-CoV-2 to other HCoVs that have led to local epidemics in the past. The experience acquired in SARS and MERS epidemics may prove useful in understanding the SARS-CoV-2 pathomechanism and lead to effective treatment and potential vaccine development. This study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 124 publications
(222 reference statements)
0
6
0
Order By: Relevance
“…Decreased serum cytokine levels have been reported to correlate with recovery from SARS-induced pneumonia. On the contrary, elevated levels of IL-4, IL-5, and IL-10 have been associated with fatal cases of SARS [36]. This cytokine response has been demonstrated with other viruses.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Decreased serum cytokine levels have been reported to correlate with recovery from SARS-induced pneumonia. On the contrary, elevated levels of IL-4, IL-5, and IL-10 have been associated with fatal cases of SARS [36]. This cytokine response has been demonstrated with other viruses.…”
Section: Discussionmentioning
confidence: 95%
“…This cytokine response has been demonstrated with other viruses. Thus, in MERS-CoV, the increased secretion of IL-1, IL-6, IL-8, IL-12, and IFN, has been documented as a consequence of an antiviral and inflammatory response [36]. In addition, it has been shown that in, MERS-CoV the cytokines IL-8 and IL-12 are produced in greater amounts compared to the response to SARS-CoV [37].…”
Section: Discussionmentioning
confidence: 99%
“…12 13 For instance, experiences and innovation from previous infectious respiratory epidemics such Severe Acute Respiratory Syndrome(SARS) and Middle East respiratory syndrome (MERS) in LMICs, were not given due consideration in the COVID-19 pandemic, yet they could have helped in understanding and treating COVID-19. 14 15 LMIC to HIC innovation transfer is also viewed with trepidation by some in LMICs, who fear, due to past experience, that they will be treated unfairly and unequally in the transfer of the technology due in part to the deep structural inequities and power imbalances that persist between HIC and LMIC institutional partnerships. 16 17 Therefore, this scoping review seeks to identify cases of health innovation transfer from LMICs to HICs, shedding light on the frameworks and methods used in the transfer process while also identifying the obstacles, which have been recorded.…”
Section: What This Study Addsmentioning
confidence: 99%
“…Thus far the idea that an innovation developed for and by LMICs can be used to address health needs in a HIC is not yet a concept that everyone accepts, and it can be met with scepticism by some in HICs who believe, sometimes due to lack of information or bias, that only HICs can produce high-quality innovations 12 13. For instance, experiences and innovation from previous infectious respiratory epidemics such Severe Acute Respiratory Syndrome(SARS) and Middle East respiratory syndrome (MERS) in LMICs, were not given due consideration in the COVID-19 pandemic, yet they could have helped in understanding and treating COVID-19 14 15. LMIC to HIC innovation transfer is also viewed with trepidation by some in LMICs, who fear, due to past experience, that they will be treated unfairly and unequally in the transfer of the technology due in part to the deep structural inequities and power imbalances that persist between HIC and LMIC institutional partnerships 16 17.…”
Section: Introductionmentioning
confidence: 99%
“…In this review paper, SARS-CoV-1, MERS and SARS-CoV-2 are studied to follow the long-term consequences of these lineage B species of coronaviruses. Table 1 represents the comparative analysis of CoVs that cause differences in the epidemic scale and the severity of the consequences [ 9 , 10 , 11 , 12 , 13 , 14 , 15 ].…”
Section: Taxonomy Of Coronavirusesmentioning
confidence: 99%